(untitled) (Bangladesh Journal of Child Health, 2020)
Background: Correct positioning and attachment play a crucial role in the successful establishment and maintenance of breast feeding. Objective of this study was to determine the effectiveness of immediate postnatal training of the mothers on their practice of proper positioning and attachment during breast feeding. Material and Methods: This one group pretest-posttest quasi-experimental study was conducted at the Department of Pediatrics and Department of Obstetrics and Gynecology of Chittagong Medical College Hospital from January 2006 to June 2006. Three hundred mothers were evaluated for breast feeding position and attachment within 6 hours following normal delivery with a questionnaire and observational checklist. Then they received training on correct positioning and attachment for successful breastfeeding. Post training effect was evaluated by assessing mothers’ practice on 7th postnatal day among 256 mothers. Pre training and post training data were analyzed with SPSS-16 and McNemar test was done to see the difference. Results: Out of 256 mothers only 22.3% were first time mother and about 40% of them had 1-2 children. Majority (84.4%) of them knew about the benefits of breast feeding though one third (36.3%) of them favored pre-lacteal feeding. Statistically significant improvement in all components of position and attachment for breast feeding was found after intervention. Conclusion: The study results showed that immediate postnatal intervention towards correct positioning and attachment were highly effective for successful breast feeding. Bangladesh J Child Health 2020; VOL 44 (1) :13-17